The Urgency of Harmonizing the Regulation of the Minister of Communication and Informatics Regarding the Recycled Customer Number Policy: Urgensi Harmonisasi Peraturan Menteri Komunikasi dan Informatika Mengenai Kebijakan Nomor Pelanggan Daur Ulang - Milianty, Yessa; Sitabuana, Tundjung Herning (Indonesian Journal of Law and Economics Review, 2025)
General Background: The rapid expansion of digital services in Indonesia has transformed mobile phone numbers into core digital identifiers across banking, e-commerce, transportation, and governmental platforms. Specific Background: Under current regulations, particularly Ministerial Regulation No. 14/2018, inactive numbers may be recycled and reassigned without uniform data-sanitization procedures, exposing users to substantial privacy and security risks. Knowledge Gap: Despite the enactment of the Personal Data Protection Law, there remains regulatory disharmony between Ministerial Regulation No. 14/2018 and No. 5/2021, especially regarding conflicting timelines for data retention and number reassignment, with no standardized technical safeguards in place. Aims: This study examines the inconsistencies between these regulations and evaluates their implications for data protection, consumer security, and legal certainty. Results: Findings indicate that number-recycling practices allow residual digital identities to persist, enabling unauthorized access, data breaches, and identity theft, thereby conflicting with data-protection principles and consumer-rights provisions. Novelty: This research highlights the structural legal gap that permits overlapping identity cycles and proposes adopting a Reassigned Numbers Database model to mitigate misdirected authentication risks. Implications: Harmonizing regulatory frameworks and establishing national technical standards are urgently required to safeguard user privacy, strengthen digital-ecosystem integrity, and ensure compliance with emerging data-protection norms. Highlights: Regulatory disharmony creates legal uncertainty and heightens privacy risks. Recycled numbers enable unauthorized access to prior users’ digital accounts. A national Reassigned Numbers Database is crucial for safer digital authentication. Keywords: Number Recycling, Data Protection, Privacy, Telecommunications Regulation, Consumer Security